DINAMIKA TAFSIR NUSANTARA - Hilmi, Ahmad Alwan (LP2M Universitas PTIQ Jakarta, 2023)
Interpretation of the archipelago is a manifestation of the assessment of the Qur'an by Nusantara scholars. The emergence of tafsir al-Qur'an in the archipelago cannot be separated from the process of evaluating and writing it down as part of the Ulama' efforts to understand and spread Islamic teachings. In this context, locality also colors various nuances of interpretation of the Qur'an, both in terms of interpreting the Qur'an in prayer rooms, mosques and Islamic boarding schools or in writing interpretations using local symbols in shapes such as pegon or Latin. In another aspect, the contribution of the influence of Middle Eastern Ulama influenced many Indonesian Ulama who made a genealogy of thoughts that shaped different tendencies in each season. The locality of Nusantara tafsir has different tendencies in each period. The dynamics of methods and approaches seem to encounter an anti-climax in the contemporary period with social-community nuances. Through thematic methods and contextualist approaches, it is very different from the previous period, especially with regard to the interpretation of the themes of infidels, people of the book and non-Muslims. Interpretation of these themes in the modern period was mostly carried out to find understandings that were considered essential and contextual in accordance with the problems faced by Muslims. The pattern of social relations between religious communities becomes the centrality in the thematic discussion of the verses of kafir, ahl al-kitab and non-Muslims which at first glance is a concept of the pattern of relations between Muslims and non-Muslims in theological and social aspects.